Fiscal institutions, fiscal policy and sovereign risk premia - Mark Hallerberg; Guntram B. Wolff (Deutsche Bundesbank, 2006)
We investigate the effect of fiscal institutions such as the strength of the finance minister in the budget process and deficits on interest spreads contained in bond yields of the countries now belonging to the Eurozone. Deficits significantly increase risk premia measured by relative swap spreads. The effect of deficits is significantly lower under EMU. This effect partly results from neglecting the role of fiscal institutions. After controlling for institutional changes, fiscal policy remains a significant determinant of risk premia. We find that better institutions are connected with lower risk premia. Furthermore deficits and surpluses matter less for risk premia in countries with better institutions. This reflects the market perception, that better institutions will reduce fiscal dificulties and make the monitoring of annual developments less important. The results are robust to controlling for country fixed effects and different estimation methodologies.
Keywords: E43; H61; H62; G12; G15; E62; 330; Budget institutions; fiscal rules; sovereign risk premia; EMU; fiscal policy; government bond yields; Finanzpolitik; Regelgebundene Politik; Haushaltsdefizit; Öffentliche Schulden; Öffentliche Anleihe; Länderrisiko; Risikoprämie; Schätzung; Europäische Wirtschafts- und Währungsunion; EU-Staaten